Li Storage of Calcium Niobates for Lithium Ion Batteries - Yim, Haena; Yu, Seung-Ho; Yoo, So Yeon; Sung, Yung-Eun; Choi, Ji-Won (AMER SCIENTIFIC PUBLISHERS, 2015)
New types of niobates negative electrode were studied for using in lithium-ion batteries in order to alternate metallic lithium anodes. The potassium intercalated compound KCa2Nb3O10 and proton intercalated compound HCa2Nb3O10 were studied, and the electrochemical results showed a reversible cyclic voltammetry profile with acceptable discharge capacity. The as-prepared KCa2Nb3O10 negative electrode had a low discharge capacity caused by high overpotential, but the reversible intercalation and deintercalation reaction of lithium ions was activated after exchanging H+ ions for intercalated K+ ions. The initial discharge capacity of HCa2Nb3O10 was 54.2 mAh/g with 92.1% of coulombic efficiency, compared with 10.4 mAh/g with 70.2% of coulombic efficiency for KCa2Nb3O10 at 1 C rate. The improved electrochemical performance of the HCa2Nb3O10 was related to the lower bonding energy between proton cation and perovskite layer, which facilitate Li+ ions intercalating into the cation site, unlike potassium cation and perovskite layer. Also, this negative material can be easily exfoliated to Ca2Nb3O10 layer by using cation exchange process. Then, obtained two-dimensional nanosheets layer, which recently expected to be an advanced electrode material because of its flexibility, chemical stable, and thin film fabricable, can allow Li+ ions to diffuse between the each perovskite layer. Therefore, this new type layered perovskite niobates can be used not only bulk-type lithium ion batteries but also thin film batteries as a negative material.
Keywords: LAYERED-PEROVSKITE; ELECTROCHEMICAL PERFORMANCE; INTERLAYER; NANOSHEETS